Development and Validation of a Robust Ferroptosis-Related Gene Panel for Breast Cancer Disease-Specific Survival - Li, Pei; Yang, Benlong; Xiu, Bingqiu; Chi, Yayun; Xue, Jingyan; Wu, Jiong (Frontiers in Cell and Developmental Biology, 2021)
BACKGROUND: New biomarker combinations have been increasingly developed to ameliorate the precision of current diagnostic and therapeutic modalities. Recently, researchers have found that tumor cells are more vulnerable to ferroptosis. Furthermore, ferroptosis-related genes(FRG) are promising therapeutic targets in breast cancer patients. Therefore, this study aimed to identify ferroptosis-related genes that could predict the disease-specific survival(DSS) of breast cancer patients. METHODS: Gene expression matrix and clinical data were downloaded from public databases. We included 960 and 1,900 patients from the TCGA and METABRIC cohorts, respectively. FRG were downloaded from the FerrDb. FRG differential expression was analyzed by comparing the tumor with the adjacent normal tissues. The univariate Cox study of DSS was done to identify prognostic FRG. The TCGA-BRCA cohort was used to generate a nine-gene panel with the LASSO cox regression. The METABRIC cohort was used to validate the panel. The panel’s median cut-off value was used to divide the patients into high- or low-risk subgroups. The analysis of immune microenvironment, functional pathways, and clinical correlation were conducted via GO and KEGG analysis to determine the differences between the two subgroups. RESULTS: The DSS of the low-risk subgroup was longer than that of the high-risk subgroup. The panel’s predictive ability was confirmed by the ROC curves(TCGA cohort AUC were 0.849, 0.806, and 0.695 for 1, 2, 3, years respectively, METABRIC cohort 0.75, 0.706, and 0.734). The panel was an independent DSS prognostic indicator in the Cox regression analyses. Immune-related pathways were enriched in the high-risk subgroup(TCGA cohort: HR = 3.51, 95% CI = 1.792-6.875, P < 0.001; METABRIC cohort: HR = 1.76, 95% CI = 1.283-2.413, P < 0.001). The two subgroups that were stratified by the nine-gene panel were also associated with histology type, tumor grade, ER/PR status, HER2 status, and TNM stage. CONCLUSIONS: The new gene panel consisting of nine FRG may be used to assess the prognosis and immune status of patients with BRCA. A precise therapeutic approach can also be possible with risk stratification.